2017
DOI: 10.1159/000481525
|View full text |Cite
|
Sign up to set email alerts
|

Endocranial Casts of Pre-Mammalian Therapsids Reveal an Unexpected Neurological Diversity at the Deep Evolutionary Root of Mammals

Abstract: The origin and evolution of the mammalian brain has long been the focus of scientific enquiry. Conversely, little research has focused on the palaeoneurology of the stem group of Mammaliaformes, the Permian and Triassic non-mammaliaform Therapsida (NMT). This is because the majority of the NMT have a non-ossified braincase, making the study of their endocranial cast (sometimes called the “fossil brain”) problematic. Thus, descriptions of the morphology and size of NMT endocranial casts have been based largely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(52 citation statements)
references
References 64 publications
(182 reference statements)
1
51
0
Order By: Relevance
“…We estimated the body mass and calculated the EQs following previous protocols (Benoit, Fernandez, et al, ). The highest values of body mass estimation were provided by BMb (Hu et al, ), and the lowest by BMc (Castanhinha et al, ), as previously observed by Benoit, Fernandez, et al ().…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We estimated the body mass and calculated the EQs following previous protocols (Benoit, Fernandez, et al, ). The highest values of body mass estimation were provided by BMb (Hu et al, ), and the lowest by BMc (Castanhinha et al, ), as previously observed by Benoit, Fernandez, et al ().…”
Section: Resultsmentioning
confidence: 99%
“…In the last few years, several studies have been carried out, improving the knowledge of the endocranial morphology of several non‐mammaliaform therapsids through digital reconstruction of the endocast as follows: the biarmosuchian Lemurosaurus (Benoit, Fernandez, Manger, & Rubidge, ); the dinocephalian Moschops (Benoit, Manger, Norton, Fernandez, & Rubidge, ); the dicynodonts Pristerodon (Laaß, ), Diictodon (Laaß, Schillinger, & Kaestner, ), Kawingasaurus (Laaß & Kaestner, ), and Niassodon (Castanhinha et al, ); the gorgonopsian Cynariops (Bendel, Kammerer, Kardjilov, Fernandez, & Fröbisch, ); the early non‐mammaliaform cynodont Galesaurus (Pusch, Kammerer, & Fröbisch, ), and the prozostrodontid non‐mammaliaform cynodonts Riograndia (Rodrigues et al, ) and Brasilodon (Rodrigues, Ruf, & Schultz, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, the EQs of R. procurvidens are still lower than those of the cynodont Brasilitherium (0.14 AE 0.05 and 0.24 AE 0.09; Rodrigues et al 2013), and shows markedly less encephalization than Mammaliaformes, as seen in Hadrocodium (0.24 AE 0.08, 0.51 AE 0.19) and Morganucodon (0.20 AE 0.07, 0.35 AE 0.13) (Rowe et al 2011) (Table S1). This demonstrates the progressive increase of EQs approaching the early evolution of mammaliaforms in comparison with early Therapsida (Benoit et al 2017b(Benoit et al , 2018 (Fig. 9).…”
Section: Encephalizationmentioning
confidence: 74%
“…Posteriorly, the brain endocast descends posteroventrally so that there is a moderate degree of flexure between the forebrain and hindbrain of ~141° (Benoit et al . ). This is a lesser degree of flexion than is present in both basal burnetiamorphs ( Lemurosaurus ) and non‐burnetiamorph biarmosuchians ( Hipposaurus and Herpetoskylax ), but its prevelance in burnetiids is as yet unknown (Benoit et al .…”
Section: Basicranium and Endochondral Elementsmentioning
confidence: 97%
“…This is a lesser degree of flexion than is present in both basal burnetiamorphs ( Lemurosaurus ) and non‐burnetiamorph biarmosuchians ( Hipposaurus and Herpetoskylax ), but its prevelance in burnetiids is as yet unknown (Benoit et al . ). The bony labyrinth of SAM‐PK‐K11112 is also largely ossified, as in other biarmosuchians and dinocephalians (Benoit et al .…”
Section: Basicranium and Endochondral Elementsmentioning
confidence: 97%